Thursday

April 24, 2014

April 24, 2014

Posted by **sonia** on Thursday, October 22, 2009 at 8:50pm.

f(-1)=

f(2)=

- algebra -
**bobpursley**, Thursday, October 22, 2009 at 9:08pmI dont see your problem.

I will be happy to check your figuring.

**Related Questions**

algebra - find the indicated outputs for f(x)= 4x-5x= f(0)= f(-1)= f(2)=

Algebra 1 - Find the indicated outputs for f(x)=4x(2)-5x f(0)=? f(-1)=? (f(2)=?

Algebra - I need help finding the the indicated outputs for f(x)=4x^-5x f(0) f(-...

math - Function k(x) = x+18 Find k(0) k(x) = 6x k(-2) k(5) k(-2) indicated ...

algebra - Find the indicated outputs for f(x) =4x^2 -4x f(0) f(-1) f(2)

algebra - Find the indicated outputs for f(x)=4x^2 -4x f(0) f(-1) f(2)

algebra - find the indicated outputs for f(x = 3x^2 -5x f(0)= f(-1)= f (2)=

Algebra - Find the indicated outputs for f(x)=¡¼5x¡½^(2 )-2x f(0)= f(-1)= f(2)=

algebra - find the indicated outputs for f(x)5^2-4x F(0)= f(-1)= f(2)=

Algebra - Find the indicated outputs for f(x)= 5 x(2) - 4x. F(0)= f(-1)= f(2)=